Oxford Handbook of Respiratory Nursing - Robinson, Terry A. (Oxford Handbooks in Nursing Ser, 2021)
Offering a systematic description of the main respiratory diseases found in adults, the Handbook covers the assessment, diagnosis, and nursing management of each condition. The Oxford Handbook of Respiratory Nursing second edition is a unique and invaluable companion for all healthcare professionals working within the specialty